Four-factor optimization for PET glycolysis with consideration of the effect of sodium bicarbonate catalyst using response surface methodology. (September 2020) - Van-Pham, Dan-Thuy; Le, Quoc-Hien; Lam, Tuyet-Nhi; Nguyen, Chanh-Nghiem; Sakai, Wataru
Abstract: In this study, Response Surface Methodology based on four-factor Box-Behnken design was applied to suggest the optimal conditions for glycolysis of polyethylene terephthalate (PET) and to analyze the individual and interaction effects of the factors on the process. Four independent factors of interest, namely reaction time (3–5 h), reaction temperature (192–200 °C), mass ratio of ethylene glycol (EG) to PET (2.5–7.5), and mass ratio of sodium bicarbonate (NaHCO3 ) to PET (0.6–1.0%), were under consideration for their catalyst effect on the process. A regression model as a mathematical function of the four factors was obtained to predict the yield of bis(2-hydroxyethyl) terephthalate (BHET) yield and its reliability was evaluated by analysis of variance. A remarkably high yield of 75.7% was obtained with 1.3% error from the predicted value at the optimal operating conditions for temperature, time, EG:PET mass ratio, and NaHCO3 :PET mass ratio of 192 °C, 3.02 h, 6.09 and 0.82%, respectively. The experimental results and analysis of response surfaces revealed that an inappropriately large amount of catalyst might restrict monomer conversion under excess EG conditions. Moreover, PET glycolysis process could be carried out under lower temperature and shorter time due to the profound effect of excess EG at a suitable concentration level of NaHCO3 . This suggested future in-depth analysis with wider parameter space to optimize PET glycolysis under conditions of large amount of EG and to gain insight into the interaction effect between EG amount and catalyst concentration. Highlights: An optimal amount of EG could facilitate monomer conversion at a sufficient concentration level of NaHCO3 catalyst. Under excess EG conditions, an inappropriately large amount of NaHCO3 might restrict monomer conversion. Appreciable BHET yield was obtained at low reaction temperature and short reaction time at the cost of excess EG. Prolonged glycolysis at lower reaction temperature might reduce BHET yield if large amount of EG had been provided.